We are not alone: AGNES, developing a prototype to support communication between schools and student transgender women - Raulino, Natã Lael Gomes; Saboia, Inga; Nunes, Caio Eduardo Pereira; de Lima, Gabriely Rodrigues; Soares, Lucas Lopes (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2021: Anais do XX Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2021)
Brazilian transgender women face high schools dropoutrates in basic education. Brazil has 82% of school dropout rates on transgender women. This situation increases the vulnerability of this population and deepens violence rates against them. This context is influenced, among other factors, by the lack of support within the educational environment. A prototype for a mobile application named AGNES was designed based on a formative research. The goal of this application is a better communication and promoting a community sense between schools and student transgender women. This article aims to report the process development andusability tests of AGNES. The prototyping process was based on Garrett’s 5-plane framework for user experience productdevelopment. Usability and satisfaction parameters were tested in a development cycle. The test was based on a preliminary survey, a Think Aloud protocol, the System Usability Scale (SUS) and an open-ended interview. The results were positive and proved a high usability with the volunteers stating that AGNES is easy to use and would be used frequently. This research project revealed that this public needs a solution to help decrease the school dropout rates. Besides, the volunteers showed satisfaction with this type of solution.